Molecular characterization and antimicrobial resistance profiling of Salmonella enterica subsp. enterica isolated from ‘selom’ (Oenanthe stolonifera) - Lee, Learn Han; Cheah, Yoke Kqueen; Mohd Sidik, Shiran; Sukardi, Sabrina; Awang Salleh, Noorzaleha; Sim, Jiun Horng; Khoo, Chai Hoon; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Fifty-nine isolates of Salmonella enterica subsp. enterica (S. enterica) isolated from indigenous vegetables, ‘selom’ (Oenanthe stolonifera) associated with 13 different serovars were obtained from Chemistry Department of Malaysia. The isolates encompass the common serovar, Salmonella enterica subsp. enterica serovar Weltevreden (S. Weltevreden) (39%) and Salmonella enterica subsp. enterica serovar Agona (S. Agona) (8.5%). Frequencies of the other 11 Salmonella serovars were ranged from 1.7% to 5.1%. All isolates were characterized by Enterobacterial Repetitive Intergenic Consensus-Polymerase Chain Reaction (ERIC-PCR), random amplified polymorphic DNA (RAPD), plasmid profiling and antimicrobial susceptibility testing. The results demonstrated ERIC-PCR, RAPD and composite analysis of both are suitable typing methods for S. enterica by demonstrating good discriminative ability and can be utilize as a rapid approach of comparing S. enterica isolates for epidemiological investigation. From this study, ERIC-PCR is exhibited lower discriminatory power when compare with RAPD. On the other hand, plasmid profiles yielded 32 profiles with molecular size ranging from 1129 bp to 17911 bp. Thirteen antimicrobial agents were included in this study and all isolates showed 100% (59/59) resistant to erythromycin and showed Multiple Antimicrobial Resistance (MAR) indexes ranging from 0.08 to 0.68. Dendrogram generated from antimicrobial resistance profiling exhibited poor discriminatory capability at serovar level. Although poultry still remain as the common reservoir for multidrug resistant (MDR) Salmonella. The isolation of 13 Salmonella serovars from selom that showed high MDR in this study is alarming. These results supported the notion that indigenous vegetable (selom) are gaining more antimicrobial resistance and could be potential health hazards.